SLU Aqua Institute of Freshwater Research Swedish Electrofishing Registry - SERS - Anders Kinnerbäck (Swedish University of Agricultural Sciences, 2010)
Electrofishing is a quantitative method to monitor the fish fauna in running waters, allowing fish to be released back alive. SERS consists of results from 81 000 electrofishing occasions all over Sweden, as far as back to the 1950’s. The Department of Aquatic Resources (SLU Aqua) at the Swedish University of Agricultural Sciences is responsible of collecting and quality assuring test-fishing data generated in national and regional environmental programs, on behalf of the Swedish Agency for Marine and Water Management. The purpose is to facilitate the access of high quality data for research, national investigations and reports. The database also serves as a reference for local and regional investigations. All data is available for the public (www.slu.se/elfiskeregistret).
Keywords: Occurrence; Observation; Sweden; Pisces; Running waters; Electrofishing; Fish; Freshwater; Occurrence; OCCURRENCE; Biological Sciences; Biologi; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser